Exploring the Role of School Principals in Promoting Entrepreneurship in Kindergartens: A Study in Kuta Alam, Banda Aceh - Susanti, Sri; Usman, Nasir; Niswanto, Niswanto (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
School principals have a strategic role in introducing entrepreneurship to teachers. This research aims to discover the program, strategies, and supporting factors and obstacles for school principals in introducing entrepreneurship in kindergarten at the Kuta Alam District Activity Center (PKG) in Banda Aceh. This research uses a descriptive method with a qualitative approach, with data collection techniques of interviews, observation, and documentation studies. The data analysis technique used is descriptive analysis. The research results showed that the program to introduce entrepreneurship had been prepared at the beginning of the semester, involving the principal, senior teachers, and supervisors. Still, they were not complete and not well-detailed. The principal's strategy for introducing entrepreneurship is to involve all school personnel. This activity is part of the implementation of P5 in the independent curriculum, such as implementing market day. This study contributes by providing insight into the importance of careful planning and structural support to strengthen the implementation of entrepreneurship programs in early childhood education. The implication is the need for policies that encourage ongoing training for teachers and adequate funding for the program's success to build an entrepreneurial culture from an early age in the educational environment.